GAME EDUKASI MATCH PUZZLE MENGGUNAKAN ALGORITMA FISHER-YATES SHUFFLE BERBASIS ANDROID - Virginia, Maria; Ginting, Jusia Amanda (Jurnal Algoritma, Logika dan Komputasi, 2023)
Games are one of the entertainment facilities that are in great demand by various groups and ages. Not just games, games can also be an interesting learning intermediary so that the learning process becomes more enjoyable. The use of games as a learning intermediary can improve the quality of learning because children are not easily bored in teaching and learning activities. A game that is suitable to support the quality of children's learning is a puzzle game where puzzle games train children to focus and solve the puzzles. The algorithm used to create the puzzle game is Fisher-Yates Shuffle. The Fisher-Yates Shuffle method is an algorithm that generates random permutations of an infinite set, in other words to randomize a set. The result of this research is an android-based puzzle educational game that implements the Fisher-Yates Shuffle algorithm to randomize puzzle objects so that users cannot memorize the position of objects.